Molybdenum and tungsten carbides can shine too. Issue 18 (7th September 2020) - Führer, M.; van Haasterecht, T.; Bitter, J. H.
Abstract : In this perspective, we argue that transition metal carbides such as molybdenum and tungsten hold great potential for the catalytic conversions of future feedstocks due to their ability to remain active in the presence of impurities in the feedstock. Abstract : In this perspective, we argue that carbides of transition metals such as molybdenum and tungsten hold great potential for the catalytic conversions of future feedstocks due to their ability to remain active in the presence of impurities in the feedstock. The presence of N and S impurities, found in increasing amounts in fossil-based feedstocks and also in new renewable feedstocks (such as biomass) may cause the carbides to convert to their respective nitrides or sulphides. These phases are catalytically active for similar reactions to the carbides and so these impurities would not lead to complete catalyst deactivation as they do for noble metal catalysts. Establishing the full potential of transition metal carbides as catalysts requires studies that use real feedstocks to look into the role of heteroatoms during the processing of fossil and novel feedstocks.